MEDIA EDUKATIF TEKA-TEKI SILANG DALAM PEMBELAJARAN SOSIOLOGI DI KELAS X IPS SMA N 13 PADANG - Arian Arian (Horizon, 2021)
His research is based on the lack of innovation of teachers in preparing instructional media in preparing lesson plans. This study aims to 1) describe the learning design using the crossword puzzle media 2) describe the learning scenario using the cross puzzle 3) compile the form of learning evaluation tools using the crossword puzzle media. The method used in this research is a qualitative approach method, in the form of descriptive, using data collection techniques in this study are documents, observation and interviews and literature study. data analysis through the stages of data collection, data presentation, and drawing conclusions. The results of the research conducted at SMA Negeri 13 Padang, researchers 1) Planning learning with educational media Cross Puzzle the results formulate learning objectives. The results of the research design used the cognitive domain at the level of understanding and analysis. Students understand the concepts and facts in the material and a crossword puzzle box will be made which is filled in by students down and horizontally for each material explained. 2)     Creating a learning scenario arranges the time allocation from the initial activity, and the core activity has the nuances of Cross Puzzle students are able to explain and analyze each indicator, for that it will be tested using Cross Puzzle filling in the empty boxes horizontally and descending and closing the learning 3) Determine the form of evaluation tool in the form of essay questions that students will do at the end of each less.